2013
DOI: 10.1159/000346076
|View full text |Cite
|
Sign up to set email alerts
|

Apathy Secondary to Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: Apathy is a disturbance of motivation, frequent in survivors of stroke. Several studies have evaluated the rate of apathy secondary to stroke and risk factors. Different conclusions and contradictory findings have been published. We aimed to perform a systematic review and meta-analysis of all studies evaluating apathy secondary to stroke to better estimate its rate and risk factors, and explore associations with poorer outcomes. Methods: We searched PubMed, Cochrane Library, PsychINFO and PsycBITE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 96 publications
8
86
1
3
Order By: Relevance
“…66 Apathy is more common in women, 65 in studies using clinician-ratings compared to self-ratings or informant-ratings, 65 and in recurrent strokes. 66 We identified three prospective studies (recruiting 408, 106 and 145 stroke patients), but methodological differences make direct comparisons difficult. The proportion whose apathy had remitted at follow-up ranged from 44% 67 to 67% 68 .…”
Section: Apathymentioning
confidence: 99%
“…66 Apathy is more common in women, 65 in studies using clinician-ratings compared to self-ratings or informant-ratings, 65 and in recurrent strokes. 66 We identified three prospective studies (recruiting 408, 106 and 145 stroke patients), but methodological differences make direct comparisons difficult. The proportion whose apathy had remitted at follow-up ranged from 44% 67 to 67% 68 .…”
Section: Apathymentioning
confidence: 99%
“…Apathy, which is a common disturbance in stroke, is defined as a lack of motivation or interest in goal-directed activities. It is known to impair the functional level after stroke (10).…”
Section: Introductionmentioning
confidence: 99%
“…Scholten et al (2016) in a systematic review found that prevalence rates for depressive disorders after TBI are up to 21% to 57% after follow-up periods of on average 1.5 to 3 years. Apathy has been reported for 46% to 71% of adults with TBI and for 15% to 71% of adults with stroke (see for example Caeiro, Ferro, & Cosat, 2013;Lane-Brown & Tate, 2009;Van Reekum, Stuss, & Ostrander, 2005). Reported prevalence rates of behavioural and emotional problems after ABI vary.…”
Section: Introductionmentioning
confidence: 99%